Поетика заголовків п'єс Івана Тобілевича - Поліщук, Кирило; Polishchuk, Kyrylo (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто проблему поетики титулу літературного твору як особ- ливого композиційного елементу. На основі варіацій титулів простежено, як міняється опція сприймання твору, як змінюється розуміння головної ідеї. Отримані результати дослідження слугують базою для подальших досліджень у цьому напрямі.The article investigates the problem of poetics title of a literary work as a special and very important compositional element. Title of dramatic works unlike the title lyric or epic work is a specific and complicated part of composition. Quite often, the title of plays is directly related to its main creative unit that is a backbone factor. The purpose of the article – explore the features headers plays by John Tobilevych and trace how the author looking for optimal title of the play. It is known that for various reasons the oppression of censorship, alterations dramas own creative research Tobilevych had to change the titles of their plays. On the basis of variations titles we have traced how changing perception option, works like shifting aspects of one problem to another, from one to another hero like changing understanding the main idea. Notable in article covers the theoretical part of the poetics of titles in drama. This research study is important and promising, because the headlines of plays by Ivan Tobilevych before are not become the subject of some research. The results of research will not only expanding the understanding of compositional harmony and optimal organization Tobilevych’s dramatic works, but some serve as the basis for further research in this direction.
Poetics of Titles of Ivan Tobilevych’s Plays
Keywords: поетика; титул; Іван Тобілевич; драматургічна майстерність; оптимальна організація; системотворчий чинник; poetics; titles; Ivan Tobilevych; dramatic art; optimal organization; factor of forming system